Opportunities and Challenges of Implementing a Jigsaw Type Cooperative Learning Model on Two Variable Linear Equation System Material - Paliling, Jein Putri; Tandililing, Pitriana; Panjaitan, Agnes Teresa (IJBLE Scientific Publications Community Inc., 2024)
This study aims to describe the opportunities and challenges of implementing Jigsaw-type cooperative learning on the material of Two Variable Linear Equation Systems. The subjects of this study were all 27 grade VIII students of Yedam Abepura Junior High School. Data collection techniques use data triangulation, namely by observation techniques, student worksheet data and interviews. The results of this study showed that the opportunity to apply Jigsaw-type cooperative learning to the material of the two-variable linear equation system received a positive response from all students, enthusiastic and enthusiastic students in doing tests on worksheets based on observations. The implementation process went well and smoothly and was completed on time. For satisfaction, teachers and students are quite satisfied with the results obtained. The challenge in implementing this Jigsaw type cooperative learning model is that there are differences in students' basic academic abilities or in other words, students' basic abilities, especially Mathematics learning, vary so that when learning the Jigsaw model cooperative model, students who do not understand need to get extra explanations with additional long time compared to students who already have a good academic ability foundation finish faster and wait queue of friends who have not moved from another group during explaining the material. Then the odd number of students also causes difficulty dividing in groups evenly.